2000
DOI: 10.1001/jama.284.13.1655
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Cost-Benefit of Influenza Vaccination of Healthy Working Adults

Abstract: Influenza vaccination of healthy working adults younger than 65 years can reduce the rates of ILI, lost workdays, and physician visits during years when the vaccine and circulating viruses are similar, but vaccination may not provide overall economic benefits in most years. JAMA. 2000;284:1655-1663.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
370
2
22

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(410 citation statements)
references
References 31 publications
16
370
2
22
Order By: Relevance
“…Since there were no data for pregnant women, it was assumed that healthy pregnant women had the same risk of clinical influenza as other healthy adults. Five studies [31][32][33][34][35] were identified as being relevant as they were published after 1990, actively followed a cohort of healthy adults for clinical respiratory symptoms and incorporated laboratory confirmation of influenza infection (see Table 1). All five were based in the United States.…”
Section: Deaths the Hes Database Recorded 28 Deaths Between 2001 Andmentioning
confidence: 99%
“…Since there were no data for pregnant women, it was assumed that healthy pregnant women had the same risk of clinical influenza as other healthy adults. Five studies [31][32][33][34][35] were identified as being relevant as they were published after 1990, actively followed a cohort of healthy adults for clinical respiratory symptoms and incorporated laboratory confirmation of influenza infection (see Table 1). All five were based in the United States.…”
Section: Deaths the Hes Database Recorded 28 Deaths Between 2001 Andmentioning
confidence: 99%
“…As influenza evolves from year to year, antigenic differences between previously and currently circulating strains contribute to low vaccine efficacy [1][2][3][4] and high incidence of influenza illness [2,5]. While vaccines regularly undergo reformulation to address this mismatch, vaccines may also affect antigenic evolution.…”
Section: Introductionmentioning
confidence: 99%
“…18 and vaccine efficacy can be as high as 86% when the vaccine and circulating viruses are well matched. 19 In our study, each vaccine was well matched with the circulating influenza viruses. 20 The seroprotection rates for A(H1N1) and A(H3N2) in this study increased by 27.7% and 23.5%, respectively, in the year after vaccination (Table 2).…”
Section: Discussionmentioning
confidence: 86%